Missing Heritability and Missing Co-heritability in Genomic Studies - Prem, Narain (Journal of Agronomy Research, 2021)
This methods‑focused review addresses missing heritability and co‑heritability in genomic studies, considering polygenicity, rare variants, gene–gene and gene–environment interactions, and phenotype definition. It surveys analytical strategies—from improved GWAS modeling to partitioning heritability and family‑based designs—to better capture shared genetic architecture. Recommendations emphasize data integration and robust inference to close current explanatory gaps.